Effect of smartphone use on sleep and mental health status of Indian medical students: a cross-sectional study - Haque, Shiraza; Singh, Shraddha; Narayan, Jagdish; Tripathi, Adarsh; Ahmad, Manzoor; Kumar, Toyaj; Verma, Shivam (International Journal of Research in Medical Sciences, 2024)
Background: In today's digital era, technology plays an integral role in daily life, particularly among students facing significant health challenges associated with increased screen time. The increased screen usage has been linked to deteriorating physiological and psychological well-being, contributing to physical inactivity, and a sedentary lifestyle, leading to serious health conditions such as obesity, depression, and disrupted sleep patterns. Medical students are particularly susceptible to these effects due to prolonged screen use, which compromises both their mental and physical health and increases the risk of addiction. This study aims to explore the impact of digital screen time on sleep quality, cardiometabolic health, and mental health conditions such as depression, anxiety, and stress among medical students. Method: A cross-sectional study was conducted at the Department of Physiology, KGMU, Lucknow, involving 113 medical students. Data collection utilized a structured questionnaire alongside validated instruments: PSQI for sleep quality assessment, DASS21 for psychological distress evaluation, and SAS-SV for smartphone addiction screening. Results: The findings revealed that participants reported high average smartphone usage (8.84±10.62 years) and screen time (49.98±15.17 hours weekly). Statistical analysis demonstrated significant associations between smartphone dependency (p<0.0001), psychological distress (p<0.0001), and compromised sleep quality (Global PSQI score: 6.87±3.84) highlighting prevalence of disrupted circadian rhythms and compromised health. Conclusion: This study highlights the critical need for guidelines on screen usage based on age, lifestyle, and professional demands and regulating screen use early can mitigate its detrimental health consequences, including disturbed sleep and mental health.